Władimir Sorokin w Polsce. O polskim (nie)czytaniu rosyjskiego dramatu najnowszego - Mięsowska, Lidia (Przegląd Rusycystyczny, 2020)
The main aim of this article is to present the reception of the latest Russian drama not only among the popular readers, but also among professionals. Conducted researchers prove clearly that the interest towards Russian drama has been growing recently, despite the fact that Polish readers become familiar with it through the theatre. The exemplification of presented tendencies is the oeuvre of Vladimir Sorokin ― postmodernist and scandal, finally appreciated and awarded in Russia, popular in Poland for many years. He has also gained a recognition in the word of theatre, where his controversial, but reflective dramas are being referred more and more often.